2020
DOI: 10.3389/fcell.2020.564417
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Mitochondrial-Derived Vesicles, Inflammatory Biomarkers and Amino Acids in Older Adults With Physical Frailty and Sarcopenia: A Preliminary BIOSPHERE Multi-Marker Study Using Sequential and Orthogonalized Covariance Selection – Linear Discriminant Analysis

Abstract: Physical frailty and sarcopenia (PF&S) is a prototypical geriatric condition characterized by reduced physical function and low muscle mass. The multifaceted pathophysiology of this condition recapitulates all hallmarks of aging making the identification of specific biomarkers challenging. In the present study, we explored the relationship among three processes that are thought to be involved in PF&S (i.e., systemic inflammation, amino acid dysmetabolism, and mitochondrial dysfunction). We took advantage of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 62 publications
2
29
0
Order By: Relevance
“…In the "BIOmarkers associated with Sarcopenia and Physical frailty (PF&S) in EldeRly pErsons" (BIOSPHERE) study, 11 elderly adults aged 70 years and older with PF&S and 10 non-frail and non-sarcopenic controls were included. The results of that study showed that a decline in tryptophan was one of the best predictors for discriminating older people with and without PF&S (46). Our data support those previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…In the "BIOmarkers associated with Sarcopenia and Physical frailty (PF&S) in EldeRly pErsons" (BIOSPHERE) study, 11 elderly adults aged 70 years and older with PF&S and 10 non-frail and non-sarcopenic controls were included. The results of that study showed that a decline in tryptophan was one of the best predictors for discriminating older people with and without PF&S (46). Our data support those previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…Cells harboring only mild mitochondrial defects shuttle functional mitochondria within MDVs to rescue aerobic respiration, thereby indicating a link between mitochondrial defects and EV endocytosis [ 75 , 76 , 77 , 78 ]. Mitochondrial constituents have also been found to be displaced within MDVs in age-related conditions characterized by altered cell’s quality control mechanisms [ 79 , 80 , 81 ]. MDV generation, orchestrated by mitochondrial–lysosomal crosstalk, has also been recognized as a candidate mechanism linking cellular dyshomeostasis with systemic inflammation in the context of aging and associated conditions [ 2 , 80 , 81 ].…”
Section: Altered Mitochondrial Quality Control Pathways Are Routesmentioning
confidence: 99%
“…Moreover, mitochondrial derived vesicles (MDVs) function as important mediators in the vesicle transport between mitochondria and lysosomes, which was regarded as an Drp1-independent mitophagy pathway [ 120 ]. And MDV-derived nicotinamide adenine dinucleotide may become a novel biomarker for sarcopenia [ 121 ].…”
Section: Mitochondrial Quality Control In Sarcopeniamentioning
confidence: 99%